Deletion of Mettl3 in mesenchymal stem cells promotes acute myeloid leukemia resistance to chemotherapy - Xinai Liao; Danni Cai; Jingru Liu; Haoran Hu; Ruolan You; Zhipeng Pan; Shucheng Chen; Kaiming Xu; Wei Dai; Shuxia Zhang; Xinjian Lin; Huifang Huang (Cell Death and Disease, 2023)
Abstract Acute myeloid leukemia (AML) cell survival and chemoresistance are influenced by the existence of bone marrow mesenchymal stem cells (BMMSCs); however, the pathways by which BMMSCs contribute to these processes remain unclear. We earlier revealed that methyltransferase-like 3 (METTL3) expression is significantly reduced in AML BMMSCs and that METTL3 mediates BMMSC adipogenesis to promote chemoresistance in human AML cell lines in vitro. In this investigation, we evaluated the METTL3 function in vivo. Mice exhibiting a conditional removal of Mettl3 in BMMSCs were developed by mating Prrx1-Cre ERT2 ;Mettl3 fl/+ mice with Mettl3 fl/fl mice using the CRISPR-Cas9 system. The Mettl3 deletion increased bone marrow adiposity, enhanced disease progression in the transplantation-induced MLL-AF9 AML mouse model, and chemoresistance to cytarabine. The removal of Mettl3 in BMMSCs resulted in a significant increase in BMMSC adipogenesis. This effect was attributed to the downregulation of AKT1 expression, an AKT serine/threonine kinase 1, in an m6A-dependent manner. The development of chemoresistance in AML is linked to the promoted adipogenesis of BMMSCs. We conclude that METTL3 expression in BMMSCs has a critical function in limiting AML progression and chemoresistance, providing a basis for the progression of therapeutic approaches for AML.